Australasian sky islands act as a diversity pump facilitating peripheral speciation and complex reversal from narrow endemic to widespread ecological supertramp. Issue 4 (7th March 2013) - Toussaint, Emmanuel F. A.; Sagata, Katayo; Surbakti, Suriani; Hendrich, Lars; Balke, Michael
Abstract The Australasian archipelago is biologically extremely diverse as a result of a highly puzzling geological and biological evolution. Unveiling the underlying mechanisms has never been more attainable as molecular phylogenetic and geological methods improve, and has become a research priority considering increasing human‐mediated loss of biodiversity. However, studies of finer scaled evolutionary patterns remain rare particularly for megadiverse Melanesian biota. While oceanic islands have received some attention in the region, likewise insular mountain blocks that serve as species pumps remain understudied, even though Australasia, for example, features some of the most spectacular tropical alpine habitats in the World. Here, we sequenced almost 2 kb of mitochondrial DNA from the widespread diving beetle Rhantus suturalis from across Australasia and the Indomalayan Archipelago, including remote New Guinean highlands. Based on expert taxonomy with a multigene phylogenetic backbone study, and combining molecular phylogenetics, phylogeography, divergence time estimation, and historical demography, we recover comparably low geographic signal, but complex phylogenetic relationships and population structure within R. suturalis. Four narrowly endemic New Guinea highland species are subordinated and two populations (New Guinea, New Zealand) seem to constitute cases of ongoing speciation. We reveal repeated colonization of remote mountain chains where haplotypes out of a core clade of very widespread haplotypes syntopically might occur with well‐isolated ones. These results are corroborated by a Pleistocene origin approximately 2.4 Ma ago, followed by a sudden demographic expansion 600, 000 years ago that may have been initiated through climatic adaptations. This study is a snapshot of the early stages of lineage diversification by peripatric speciation in Australasia, and supports New Guinea sky islands as cradles of evolution, in line with geological evidence suggesting very recent origin of high altitudes in the region.